2020
DOI: 10.1101/2020.05.01.20087858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internet search patterns reveal clinical course of COVID-19 disease progression and pandemic spread across 32 countries

Abstract: Background: Coronavirus disease 2019 is an emerging infectious disease.It was first reported in Wuhan, China, and then broke out on a large scale around the world.This study aimed to assess the clinical significance of two different nutritional indices in 245 patients with COVID-19. Methods:In this retrospective single-center study, we finally included 245 consecutive patients who confirmed COVID-19 in Wuhan University Zhongnan Hospital from January 1 to February 29. Cases were classified as either discharged… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These approaches have exploited information from internet and clinicians’ search engines ( 13 19 ), news reports ( 20 22 ), crowd-sourced participatory disease surveillance systems ( 23 , 24 ), Twitter microblogs ( 25 , 26 ), electronic health records ( 27 , 28 ), Wikipedia traffic ( 29 ), wearable devices ( 30 ), smartphone-connected thermometers ( 31 ), and travel websites ( 32 ) to estimate disease prevalence in near real time. Several have already been used to track COVID-19 ( 33 , 34 ). These data sources are liable to bias, however; for example, Google Search activity is sensitive to the intensity of news coverage ( 15 , 35 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have exploited information from internet and clinicians’ search engines ( 13 19 ), news reports ( 20 22 ), crowd-sourced participatory disease surveillance systems ( 23 , 24 ), Twitter microblogs ( 25 , 26 ), electronic health records ( 27 , 28 ), Wikipedia traffic ( 29 ), wearable devices ( 30 ), smartphone-connected thermometers ( 31 ), and travel websites ( 32 ) to estimate disease prevalence in near real time. Several have already been used to track COVID-19 ( 33 , 34 ). These data sources are liable to bias, however; for example, Google Search activity is sensitive to the intensity of news coverage ( 15 , 35 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results derived here studying indicated that fear of, or interest in death was the variable with the highest explanatory power in predicting internet search effort, implying that the rst concern is either to stay alive, or interest and compassion to the individuals who passed way (Du et al 2020, Lu andReis 2021). This interest was higher than any nancial related variable, or personal freedom of movement and entertainment, or every day habits.…”
Section: Discussionmentioning
confidence: 64%
“…Higgins et al [17] 18-22 days "Coronavirus Symptoms," "Coronavirus Test," "Fever," "Cough," "Coronavirus," "Runny Nose," "Dry Cough," "Sore Throat," "Chills," and "Shortness of Breath" 32 countries Google Trends Lu and Reis [18]…”
Section: Google Trends and Baidu Indexmentioning
confidence: 99%